Early Versus Delayed Oral Feeding after Uncomplicated Cesarean Section under Spinal Anesthesia: A Randomized Controlled Trial - Adamu O Ogbadua; Teddy E Agida; Godwin O Akaba; Olumide A Akitoye; Bissallah A Ekele (Nigerian Journal of Surgery, 2018)
Objective: The objective of this study is to compare the safety of early versus delayed oral feeding after uncomplicated cesarean section (CS) under spinal anesthesia. Methods: This was a randomized, controlled trial that enrolled 152 women who had uncomplicated CS under spinal anesthesia between January 2014 and June 2014. Women in the early feeding group had sips of oral fluid 6 h postoperatively while those in the delayed feeding group were on nil per oral for the first 24 h after surgery before commencement on liquid diet. Primary outcome measure was development of symptoms of paralytic ileus while secondary outcome measures included time interval to return of bowel sound, duration of hospital stay, and patients satisfaction which was determined using a visual analog score. Results: The incidence of mild ileus symptoms was similar in both groups. Early-fed group had significantly shorter mean postoperative time intervals to return of bowel sound, (7.3 h vs. 11.5 h [P = 0.005]), passage of flatus, (30.7 h vs. 37.5 h [P = 0.009]). Hospital stay was also significantly shorter in the early feeding group, (4.2 days vs. 4.9 days [P < 0.001]). Early-fed women had higher levels of satisfaction. Conclusion: Early initiation of oral feeding after uncomplicated CS under subarachnoid block is not associated with increased incidence of gastrointestinal symptoms or paralytic ileus.